Standing giants: a digital biomechanical model for bipedal postures in sauropod dinosaurs - Silva Junior, Julian C. G. (2025)
Here we explore the potential of sauropod dinosaurs to adopt a bipedal or tripodal stance using digital biomechanical modelling and finite element analysis (FEA). Seven sauropod species from diverse lineages and sizes were sampled, and 3D models of their femora were analysed under both extrinsic (body weight distribution) and intrinsic (muscular force) functional scenarios. The results indicate that smaller sauropods, like the saltasaurid titanosaur Neuquensaurus, were more capable of sustaining bipedal postures, probably due to their robust femora combined with advantageous muscle attachment areas. In contrast, larger sauropods such as Dreadnoughtus experienced higher stress levels, making bipedal postures less likely for extended periods. Our analysis provides new insights into sauropod functional evolution, highlighting that species size and morphology significantly influenced their ability to rear up, which could have played a role in behaviours such as feeding, defence and reproduction.